Design of an Einzel Lens Using Non-Classical Variation Technique - Al-Moudarris, Fatin A J; Abd Ali, Maher M; Hussein, Oday A (Al-Nahrain Journal of Science, 2012)
A computational investigation has been carried out in the field of charged-particle optics. The work is concerned with the design of einzel (unipotential) lens by using non-classical variation method under zero magnification condition.The potential field distribution of the einzel lens has been represented by the following suggested function: U (z) = exp [-C1 (z-5)2] + C2 where C1 and C2 are constants, z is the optical axis and U (z) is the axial potential distribution. The paraxial ray equation has been solved for finding the short beam trajectory of the charged particles traversing the lens.The axial potential distributions and its first and second derivatives, the optical properties such as the focal length and spherical and chromatic aberrations are determined by using non-classical variation method. The electrode shape of the einzel lens has been determined in the two dimensions.The aberrations of the electrostatic lens from our results depend on the beam trajectory of the charged particles, where the aberration is small when the beam trajectory is shorter